Determinantes sociais da saúde e qualidade de vida de pessoas que tiveram COVID-19: estudo longitudinal - Florencio, Sabrina de Souza Gurgel (2023)
Social determinants of health (DSS) influence the quality of life of people who have had COVID-19. The general objective is to evaluate the social determinants of health and the quality of life of people diagnosed with COVID-19. This is an ecological study, with a longitudinal design, of a quantitative nature. The sample consisted of 179 people who had COVID-19, living in Ceará or Maranhão. Data collection was carried out in 2021 and 2022, by sending the instruments through the Software for monitoring patients with COVID-19 and other respiratory syndromes, including a Characterization Form for people who had COVID 19, completed monthly, and the Short Form 36 (SF-36) quality of life questionnaire, administered in the second, fourth and sixth month. Monitoring was carried out via telephone, call or message via the WhatsApp application, depending on feasibility and convenience for the participant. The collected data were processed and analyzed using the Statistical Package for the Social Sciences (SPSS), version 20.0. The Friedman and Conover tests were used. Study approved by the Ethics and Research Committee. The mean age was 37.4 (±12.6) years. The majority were female (58.7%), sedentary (51.4%), non-smokers (95.5%) and alcohol drinkers (92.2%), living with more than two people in the same household (71. 0%), with the presence of people in the risk group for COVID-19 (50.3%), with higher education (complete or incomplete) (70.9%), with water supply through the general distribution network (93.9%), with a sewage system (72.1%), residing in Ceará (74.9%), residing in the interior/metropolitan region (59.8%), with an average monthly family income of up to three salaries minimum (86.6%). Better scores were achieved in the sixth month when compared to the second month in all domains of the SF-36, showing a statistically significant difference (p<0.05) in the domains of pain, vitality, social aspects and mental health. There were better quality of life scores when comparing the 2nd with the 6th month of follow-up in all DSS (p<0.05). As an example, there was a significant difference in the variable age group between 20 and 39 years, in the domains limitations due to physical aspects (p=0.045), general health status (p=0.030), social aspects (p=0.041) and mental health (p =0.017). People who practiced physical activity three to seven days a week had better quality of life scores over the six months in the vitality (p=0.048) and mental health (p=0.008) domains. People who had a general water distribution network had better quality of life scores during the six months in the domains limitations due to physical aspects (p=0.037), pain (p=0.012), vitality (p=0.009), social aspects (p =0.001) and mental health (p<0.001). It is concluded that quality of life is conditioned by the social determinants of the health of people who have had COVID-19, with an increase in quality of life scores over the months after the disease.